DEMOCRACY AND SUSTAINABLE NATIONAL DEVELOPMENT IN NIGERIA: REIMAGINING THE NEXUS - Remi Chukwudi, Okeke (European Scientific Journal, ESJ, 2014)
This study contends that democracy is at the crossroads in Nigeria. Furthermore, the paper posits that national development has altogether, only truly manifested in the inscrutable imaginations of Nigeria’s national development planners. The general objective of the study was to examine the relationship between democracy and sustainable national development in Nigeria and consequently reimagine the nexus. The specific objectives were to: (i) examine the extent to which there is politics without progress in Nigeria (ii) verify the extent to which there is democracy without development in Nigeria and (iii) recommend ways of making Nigeria’s democracy, invariably lead to sustainable national development. The theoretical framework for the study is the political economy framework. The research methodology is the critical mode of research. We argue in the study that the underpinnings of Nigeria’s brand of democracy, fully shows the tendencies of democratic capitalism, otherwise known as capitalist democracy. Findings of the study highly support the thesis that there is politics without progress in Nigeria. Furthermore, our findings justify the viewpoint that critically, there is democracy without development in Nigeria. Democracy, it is imagined in the study, must lead to the creation of new Nigerians and the core of the brand of democracy that would link democracy with development in Nigeria, has to be essentially deliberative.